The functional status of vestibular otolith and conductive pathway in patients with unilateral idiopathic sudden sensorineural hearing loss - Shen, Jiali; Ma, Xiaobao; Zhang, Qing; Chen, Jianyong; Wang, Lu; Wang, Wei; He, Kuan; Sun, Jin; Zhang, Qin; Chen, Xiangping; Duan, Maoli; Jin, Yulian; et al. (Frontiers in Neurology, 2023)
Background The cause of idiopathic sudden sensorineural hearing loss (ISSNHL) remains unknown. It has been found that the functional status of the vestibular otolith is relevant to its prognosis; however, the evaluation of the vestibular otolith (intra-labyrinth) and superior and inferior vestibular nerve pathways (retro-labyrinth) in ISSNHL patients is not well-documented. Objective This study aimed to investigate the functional status of the vestibular otolith and conductive pathway in patients with unilateral ISSNHL and analyze the correlations between vestibular evoked myogenic potentials (VEMPs) and hearing improvement after treatment. Methods A total of 50 patients with unilateral ISSNHL underwent a battery of audio-vestibular evaluations, including pure tone audiometry, middle ear function, air-conducted sound-cervical VEMP (ACS-cVEMP), ACS-ocular VEMP (ACS-oVEMP), galvanic vestibular stimulation-cervical VEMP (GVS-cVEMP), and GVS-ocular VEMP (GVS-oVEMP). The results of auditory and VEMPs were retrospectively analyzed. Results The abnormal rates of ACS-cVEMP, ACS-oVEMP, GVS-cVEMP, and GVS-oVEMP in affected ears were 30, 52, 8, and 16%, respectively. In affected ears, the abnormal rate of ACS-oVEMP was significantly higher than that of ACS-cVEMP (p = 0.025), while it was similar between GVS-cVEMP and GVS-oVEMP (p = 0.218). Compared with GVS-cVEMP, affected ears presented with a significantly higher abnormal rate of ACS-cVEMP (p = 0.005), and the abnormal rate of ACS-oVEMP was significantly higher than that of GVS-oVEMP (p < 0.001). No significant difference existed in latency and amplitude between affected and unaffected ears in ACS-VEMPs or GVS-VEMPs (p > 0.05). The abnormal rate of VEMPs in the poor recovery group was significantly higher than that of the good recovery group (p = 0.040). The abnormality percentages of ACS-oVEMP and GVS-oVEMP in the poor recovery group were significantly higher than that of the good recovery group (p = 0.004 and 0.039, respectively). The good hearing recovery rates were 76.47% in the normal VEMPs group, 58.33% in the intra-labyrinth lesion group, and 22.22% in the retro-labyrinth lesion group. Hearing recovery worsened as a greater number of abnormal VEMPs was presented. Conclusion Besides Corti's organ, the impairment of otolithic organs was prominent in patients with ISSNHL. The normal VEMPs group had the highest rate of good recovery, followed by the intra-labyrinth lesion group and the retro-labyrinth lesion group presented with the lowest recovery rate. Abnormalities in ACS-oVEMP and/or GVS-oVEMP were indicators of a poor prognosis.